ЕРХОВ Г.П. О принципах партийного труда.Действенность партийных поручений: опыт и проблемы. - М.: Политиздат, 1988. - 240 с. - Пономаренко, Г.А.; Беспалов, М.Є. (Український історичний журнал, 1989)
.